Psychological Impact of the Lockdown in Italy Due to the COVID-19 Outbreak: Are There Gender Differences? - Rania, Nadia; Coppola, Ilaria (Frontiers in Psychology, 2021)
The COVID-19 emergency has hit the whole world, finding all countries unprepared to face it. The first studies focused on the medical aspects, neglecting the psychological dimension of the populations that were forced to face changes in everyday life and in some cases to stay forcedly at home in order to reduce contagion. The present research was carried out in Italy, one of the countries hardest hit by the pandemic. The aim was to analyze the perception of happiness, mental health, and the sense of loneliness experienced by adults during the lockdown due to the COVID pandemic. Specifically, the variables will be examined in relation to gender difference, living alone, with partner, or with partner and children. The research followed a quantitative approach using an online questionnaire. The project involved 1100 subjects from whom 721 participants (75.5% women) were extrapolated. Of them, 17.3% claimed to live alone, 39.5% with their partner, and 43.1% with their partner and children. The results show that people in general experienced a lower level of happiness and mental health and higher levels of loneliness. The lockdown and pandemic condition due to COVID-19 seems to have canceled the gender differences in the perception of happiness and mental malaise while it seems to have increased the perception of loneliness experienced by males compared to the pre-pandemic condition. In addition, those who lived alone perceived a greater level of loneliness than those who lived with their partner or partner and children. Unexpectedly, no significant differences emerged regarding the level of happiness and mental health between those who had direct contact with the virus and those who did not. These data should make political decision-makers reflect on the need to pay more attention to the implications that such drastic measures as a lockdown can have on people's psychological well-being.